Community Participation and Role in the Management of Public Green Open Space (RTH) in Cihideung District, Tasikmalaya City, West Java Province - Prihatini, Juliati; Sutikno, Achmad Nur (AIBPM Publisher, 2023)
The purpose of this study is to describe and analyze the participation and role of the community in planning, implementing development, utilization, and monitoring of public green space. Data collection techniques through observation, interviews, and documentation. The results of the study show that (1) In planning Public Open Space, the participation and role of the community is relatively passive so it needs to be motivated by the Cihideung Sub-district through the District MUSRENBANG; (2) Implementation of the development and rearrangement of Public Open Space requires a commitment between the Environmental Service and the community; (3) The benefits of public green open space are tangible and intangible. Public green open space in the four sub-districts of the Cihideung subdistrict is used by the community in a variety of ways according to local wisdom; and 4) Not yet having standard rules regarding the supervision of Public Open Space, the community provides input on the importance of zoning regulations and their designations. The implication of the study is that the role of the community is very important to ensure success in managing green open spaces. Therefore, at every stage of green open space management, from preparation to utilization and monitoring of open space, community participation is absolutely required.